2020
DOI: 10.1096/fj.202000911r
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel regulation and molecular mechanism of poly (rC)‐binding protein 1 in cancer

Abstract: Poly (rC)-binding protein 1 (PCBP1), an RNA-or DNA-binding protein with a relative molecular weight of 38 kDa, which is characterized by downregulation in many cancer types. Numerous cases have indicated that PCBP1 could be considered as a tumor suppressor to inhibit tumorigenesis, development, and metastasis. In the current review, we described the multilevel regulatory roles of PCBP1, including gene transcription, alternative splicing, and translation of many cancer-related genes. Additionally, we also provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 101 publications
0
14
0
Order By: Relevance
“…It is a novel tumor-suppressive splicing factor that regulates the process of pre-mRNA, mRNA stabilization and translation [ 9 ]. By binding specifically to elements of target mRNAs with AU-rich elements or U-rich elements located in 3’-untranslated regions, PCBP1 regulates diverse gene expression [ 16 ]. Studies showed that PCBP1 protein was significantly downregulated in various primary and metastatic cancers, including gastric cancers [ 17 ], while its mRNA level remained unchanged in most cancer tissues [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is a novel tumor-suppressive splicing factor that regulates the process of pre-mRNA, mRNA stabilization and translation [ 9 ]. By binding specifically to elements of target mRNAs with AU-rich elements or U-rich elements located in 3’-untranslated regions, PCBP1 regulates diverse gene expression [ 16 ]. Studies showed that PCBP1 protein was significantly downregulated in various primary and metastatic cancers, including gastric cancers [ 17 ], while its mRNA level remained unchanged in most cancer tissues [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The decreased CLOCK/BMAL1 transcriptional activity and increased CRY1 repression activity by PCBP1 over-expression (Figure 1E) implied that PCBP1 regulates the core circadian transcription-translation negative feedback loop, which validated our hypothesis. It has been reported that PCBP1 is relevant to tumorigenesis in diverse human cancers (Choi et al, 2009;Shi et al, 2018;Zhang et al, 2020b), and circadian clocks have close interactions with cancer metabolism (Roenneberg and Merrow, 2016;Masri and Sassone-Corsi, 2018). However, the mechanism between these is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of PCBP1 to recognize and bind poly(C) DNA and RNA sequences via KH domains is critical for their function in mammalian cells. As such, PCBP1 binds to various proteins, including iron-containing polyamine pathway dioxygenase ADI1 and signal transducer and activator of transcription 3 (STAT3), and then participates in iron homeostasis, tumorigenesis, and metastasis (Yanatori et al, 2020;Zhang et al, 2020b). Together, these studies describe the complexity of distinct interacting factors that are mediated by PCBP1, which revealed that PCBP1 participate in multiple biological processes.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the antioncogene PCBP1 was reported to be an immune checkpoint required for effector T-cell function, as well as a key molecule in the conversion of the TGF-β signaling pathway from a growth factor inhibitor to a tumor growth promoter in advanced cancer stages (70). PCBP1 was also reported to be associated with the HIF and Akt signaling pathways (82,83). However, the role of miR-490-3p in the regulation of these pathways is yet to be elucidated.…”
Section: Signaling Pathways Associated With Mir-490-3p and Mir-490-5pmentioning
confidence: 99%